Analisis Bauran Pemsaran Terhadap Keputusan Mahasiswa Memilih Program Studi ( Studi di Fakultas Ekonomi Universitas Bojonegoro) - Handayani, Asih; , Dr.Suyatmini,SE.,M.Si; , Dr. Sabar Narimo, M.M., M.Pd (2017)
ASIH HANDAYANI, Q1001200010, MARKETING MIX ANALYSIS ON THE DECISION TO CHOOSE PROGRAM STUDENTS STUDY (STUDY IN THE FACULTY OF ECONOMICS UNIVERSITY BOJONEGORO). THESIS. MUHAMMADIYAH SURAKARTA UNIVERSITY This study aims to identify and analyze the influence of marketing mix consists of product, price, promotion, place, people, physical evidence and process partially or jointly against the decision of students choosing Program Development Economics Faculty of Economics, University of Bojonegoro This research method is quantitative descriptive with case studies. This study population is students of the Faculty of Economics, University of Bojonegoro number of 820 students. 100 samples were obtained by purposive sampling technique. Techniques of collecting data by distributing questionnaires. Analysis of the data in this study using descriptive statistical analysis, classic assumption test, multiple regression analysis, t test, F test, the coefficient of determination (R2) The study concluded that the partial product, price, place, promotion, physical evidence and processes significantly influence the student's decision selecting a course of economic development of the economic faculty of the University of Bojonegoro. But partially people not significant. Significant product with 0.025 significance of less than 0.05. Price significant effect with significance 0.022 less than 0.05. Place significant influence with significance 0.022 less than 0.05. Promotion significant influence with significance 0.037 less than 0.05. People not significant because of the significance of 0057 is greater than 0.05. Physical evidence significant influence with significance 0.015 less than 0.05. The process of significant influence with significance 0.034 less than 0.05. The marketing mix consists of product, price, place, promotion, people, physical evidence and process together a significant effect on student's decision selecting Development Economics Studies Program Faculty of Economics, University of Bojonegoro. Significance of 0.000 at a significance level of 5%. The amount of influence strong enough for that shown in the determination coefficient of 56.4%. Keywords : marketing mix, product, price, place, promotion, people, physical evidence, process, decision